EBV Infection in XLP1 Manifested Solely by Behavioral Aggression and Effective Treatment Using Rituximab - Michelle M. Korah-Sedgwick; Luke A. Wall (Case Reports in Immunology)
Patients with X-linked lymphoproliferative disease 1 (XLP1) are exquisitely susceptible to Epstein-Barr virus (EBV), with the first EBV infection often resulting in rapid death. In a manner not previously described, a 5-year-old patient with XLP1 presented solely with behavioral aggression, with no laboratory evidence of organ dysfunction or inflammation. Although EBV-IgM was negative, PCR confirmed the presence of EBV in both the blood and cerebrospinal fluid. MRI of the brain showed frontal lobe foci. After failure to eradicate his viremia with ganciclovir, rituximab was administered. EBV was eradicated from the blood after the second rituximab infusion and remained absent for 5 months, at which time he underwent hematopoietic stem cell transplant. Although EBV classically produces fulminant infection in patients with XLP1, this case demonstrates that EBV infection may be initially subtle. Acute change in behavior should prompt evaluation. This case also demonstrates the possible effectiveness of rituximab in the treatment of acute EBV infection.